(untitled) (Muara Nada: Jurnal Pendidikan Seni, 2026)
This study is based on the challenges faced by beginner students in learning classical guitar, which commonly relies on standard notation. Such notation is often difficult to understand, thus hindering the learning process. To address this issue, tablature was chosen as an alternative learning medium that is more practical and easier to grasp. The research problem focuses on the process and outcomes of classical guitar learning using tablature with the piece Romance de Amor for second-semester students of the Music Education Program at UNWIRA. This research employed a qualitative approach with a field action method, involving five students who were willing to participate in intensive learning sessions. Data were collected through observation, in-depth interviews, and documentation. The learning process included the introduction of tablature, basic technique exercises, mastery of the musical piece, and final evaluation. The results showed that tablature significantly helped students understand and practice classical guitar techniques without the burden of complex music theory. There was notable improvement in playing technique, rhythm accuracy, tempo, musical interpretation, and students’ confidence. In conclusion, tablature is an effective learning medium for teaching classical guitar to beginners and can serve as a reference for music educators in developing more adaptive and innovative instrumental teaching methods in academic settings.